Identification and characterization of the genetic determinants for yellow fever virus infection and dissemination in Aedes aegypti - Huang, Yan-Jang (Kansas State University, 2014)
The genetic composition of arboviruses is a critical determinant of viral infectivity and the capacity for virus dissemination in arthropod vectors. Due to concerns related to a hypothetical potential for loss of attenuation, the supression of vector infection and dissemination is a critical component for the rationale-based design of live-attenuated flavivirus vaccine candidates. The yellow fever virus (YFV) 17D vaccine virus is not only attenuated in vertebrates, but also has low infectivity for Aedes agypti mosquitoes and since it does not disseminate, it is not transmissible. Using a reverse genetics system, the mutations present in the envelope protein YFV 17D virus were characterized in Ae. aegypti to determine the role of mutations in limiting the viral infectivity and dissemination capacity. This knowledge would contribute to the rational design of live attenuated vaccines with the desirable phenotype of being nontransmissible by arthropod vectors. The upper lateral portion of the YFV 17D envelope (E) protein domain III (EDIII) habors the T380R mutation in the FG loop. Experiments demonstrated that the T380R mutation was associated with the viral infectivity phenotype for mosquitoes, but did not influence dissemination into the secondary tissues. The G52R mutation in the molecular hinge region that is located between E protein domains I (EDI) and II, significantly reduced viral infectivity for mosquitoes. In contrast, when cloned into the Asibi wildtype virus genetic backbone, the T173I mutation in the loop structure between the G0 and H0 β- strands did not attenuate viral infection and dissemination. The double mutant virus containing both the G52R and T173I mutations in the E protein, showed a similar attenuated reduced infectivity to the single G52R mutant. The M299I mutation in the linker region between EDI and EDIII resulted in a significantly lower viral infectivity at the initial phase of viral infection at 7 days post-infection in Ae. aegypti. In conclusion, the characterization on four mutations in the YFV 17D vaccine E protein have demonstrated three genetic loci, that can influence the process of YFV infection in Ae. aegypti. These results provide new knowledge and understanding which may have broad applications for the rationale design of safe flavivirus vaccines, via targeting genetic loci and introducing specific mutations that preclude infection of, and transmission by arthropod vectors.
Keywords: Yellow fever virus; 17D vaccines; Aedes aegypti; Virology (0720)